Peran Budaya Organisasi dan Lingkungan Kerja Untuk Meningkatkan Kepuasan Kerja - Setiawati, Ni Komang; Mashyuni, I A (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
Job satisfaction is an individual thing because each individual will have a different level of satisfaction according to the values ​​that apply to each individual. In building employee job satisfaction is influenced by several factors such as organizational culture and work environment. The purpose of this study was to determine the effect of organizational culture and work environment on job satisfaction. The location of this research is at the Ubung Kaja Village Office. Questionnaires that have been tested for validity and reliability are given to 49 respondents who are employees of the Ubung Kaja Village Office. The data analysis technique used in this research is Multiple Linear Regression. Based on the results of the study, it can be seen that organizational culture has a significant positive effect on job satisfaction, and the work environment has a significant positive effect on job satisfaction. The advice that can be given to this researcher is that the Ubung Kaja Village Office should guide employees, repair or renew work facilities that are not able to support the course of work, always provide a comfortable work environment and appropriate compensation so that employees have high loyalty.